Fostering Critical Thinking Skills in Discovery Learning: The Role of a Covalent Bond Simulator - Rosida, Riani Damay; Gumilar, Gun Gun; Nais, Miarti Khikmatun; Rohman, Ijang; Hana, Muhamad Nurul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Critical thinking skills are among the 21st-century competencies that need to be fostered in science education. The abstract nature of the covalent bond concept continues to cause difficulties and misconceptions, potentially hindering the development of critical thinking skills. This study aimed to analyze the role of a feedback-based covalent bond simulator integrated with the Discovery Learning model in fostering students' critical thinking skills. A one-group pre-test post-test design was employed, involving 22 Grade 11 students from a public high school in Bandung. Data were collected using a critical thinking skills test based on Robert Ennis's indicators and analyzed using the Shapiro-Wilk test, Paired Sample t-Test, and Wilcoxon test. The results showed that the mean critical thinking skills score increased from 10.27 to 18.50. Based on the paired-samples t-test, a statistically significant difference was found between the pre-test and post-test scores (t = -6.475; df = 21; p < 0.001), and all critical thinking skill indicators showed significant improvement (p < 0.05). These findings provide preliminary evidence that integrating the simulator with Discovery Learning plays a role in facilitating students' critical thinking skills and supporting conceptual understanding for advanced chemistry learning.